Internal Control System and Hazard Identification of Operational Risk in Malaysian Conventional Banking - Noor Fareen Abdul rahim; Abdul Rahman Jaafar; Jauriyah Syamsuddin; Mohammad Nizam Sarkawi (International Journal of Supply Chain Management, 2017)
maintain competitiveness in the market, has assumed the necessity of risk management as the main pillar of modern banking in the institutes of monetary intermediation. Banks relied almost exclusively upon internal control system within business lines, supplemented by the audit function, to manage operational risk. Operational Risk Management encompasses the mechanisms, tools, policies, procedures and processes, including management oversight, to identify, assess, monitor, report, and control operational risk. The first step in the operational risk management process is to identify the hazard that is associated with risk to which the bank is exposed. Consequently, this article examines the relationship between internal control system and the hazard identification of operational risk in Malaysian conventional banks. Survey questionnaires were emailed to branch managers and assistant managers of 650 local commercial bank branches across Malaysia and 132 fully completed survey questionnaires were received. Besides, data was analyzed using multiple regressions. Importantly, the study found that Malaysian conventional banks have a good internal control system and hazard identification with a mean of 4.71 and 4.37 respectively. Moreover, there were mixed findings between the relationship of internal control system and hazard identification. Notably, the implementation of risk assessment, top management information and communication, branch information and communication and top management monitoring were found to have a significant result in the documentation of hazard identification and control decision, while implementation of risk assessment has a significant relationship with practice of hazard identification. It can be seen that top management monitoring is an important factor that influence documentation of hazard identification of operational risk in Malaysian local conventional banks.